Influence of atropine and loperamide on reduced intestinal transit induced by calotropis procera latex in rats (2006)
The effects of Calotropis procera latex alone and in the presence of loperamide and atropine on intestinal transit in rats were determined to elucidate the action of C. procera on intestinal transit. Six groups of rats containing ten rats per group were used. Each rat in the control group (I) received 0.5 ml of normal saline. Each rat in groups II, III, and IV received 0.25 ml/100 g, 0.5 ml/100g and 1.0 ml/100g of C. procera latex respectively. Thirty minutes before the administration of 0.25 ml of latex of C. procera, each rat in groups V and VI received 0.4 mg/100g atropine sulfate and 0.1 mg/100g loperamide hydrochloride respectively. Intestinal transit was measured in all animals by charcoal meal test and was expressed as the percentage of the distance traveled relative to the entire length of the intestine from the pyloric junction to the anal orifice. The mean transit point of the dye in the control group was 85.19 ± 8.51%. For Calotropis procera treated rats, the mean transit points were 68.47 ± 6.37%, 54.49 ± 6.67% and 25.06 ± 4.79% for 0.25 ml/100g, 0.5 ml/100g and 1.0 ml/100g of the latex respectively. The mean transit points in the groups pretreated with 0.4 mg/100 g atropine (Group V) and 0.1 mg/100 g loperamide (Group VI) were 55.29 ± 5.09% and 66.87 ± 6.20% respectively. The results showed that the latex of Calotropis procera inhibited intestinal motility and its action was potentiated by atropine and loperamide. This inhibitory action is contradictory to the observation of diarrhea in fed animals.